TEKNIK PENGEMASAN ABON SAPI PADA PRODI AAT (AGRIBISNIS ANEKA TERNAK) DAN PEMASARAN MELALUI WEBSITE DI SMKS DARUL ULUM LAYOA KABUPATEN BANTAENG - Andrew Ridow Johanis M; Nurdiana, Muhammad Khaddafy, Fachriyahthul Jannah, Marsha (JOURNAL OF COMMUNITY DEDICATION, 2022)
Product packaging and marketing techniques are important elements that affect the amount of consumer demand and increase sales of a product, Darul Ulum Layaa Vocational School has one of the study programs, namely agribusiness of various livestock (AAT) which externally produces valuable products such as beef jerky, shredded beef and fresh beef, all of which are the result of AAT (various livestock agribusiness) study programs at DARUL ULUM LAYOA Vocational School, Bantaeng Regency, in order to support the productivity of the study program, it is necessary to carry out a training in the form of packaging and marketing through the school's website. increase the productivity of SMK students and especially the AAT Study Program (various livestock agribusiness). Good packaging is very important to increase sales of food products as well as packaging design can affect people's buying interest as well as the use of packaging labels which are the identity of our products, packaging and packaging labels not only as wrappers but also play a role as marketing aids, product imaging displaying legal identity and as a source of product information to consumers as well as results or with marketing techniques with the current competitive situation designing a unique packaging and utilizing marketing through the school's website is an added value that functions as a promotional medium for both the product produced and for the school is to attract more New Students, Currently the students of Darul Ulum Layoa Vocational School still use or have minimal knowledge about packaging and marketing techniques through the school website and only use traditional marketing with this service activity being carried out. So it is hoped that it can provide knowledge and help Darul Ulum Vocational students in carrying out packaging and digital marketing through the school's website to increase sales also put pressure on students who want to continue their education at the high school level so that it is promising.